Politik Luar Negeri Indonesia: Refleksi dan Prediksi 10 Tahun - Wuryandari, Ganewati (Jurnal Penelitian Politik, 2008)
In the last ten years, Indonesia has seen some principal changes in international and domestic affairs. As a result, Indonesian foreign policy need to be harmonized with these changes for contemporary and fixture interests. Ideally, this harmonization need to be addressed in conceptual fr ainework and foreign policy strategy which refers to national interests projection based on priority scale and national capabilities' reality. In a reflective way, this paper was looking back to the way Indonesian foreign policy in the reform era (1998-2008) responded to some international and domestic changes and how Indonesian foreign policy direction in the nest ten years might be that is based on future issues, problems and global challenges which potentially influence Indonesian foreign policy.